Contact sensitivity to metals (chromium, cobalt and nickel) in childhood Alergia de contato aos metais (cromo, cobalto e níquel) na infância - Marilda Helena Toledo Brandão; Bernardo Gontijo (Sociedade Brasileira de Dermatologia, 2012)
Metals, especially nickel, are the most common contact allergens in children. Recent data has shown increased incidence of allergy in industrialized countries. Sensitization can occur at any age, even in neonates. Costume jewelry, particularly earrings, is linked to increased sensitization to nickel. Sensitization to cobalt often occurs by the use of costume jewelry. The most common source of sensitization to chromium is leather. Due to the absence of a specific therapy, the main treatment is to identify and avoid the responsible allergens. This article presents an updated view on the epidemiological and clinical aspects of contact allergy to metals, focusing on prevention strategies and risk factors, and warns about possible and new sources of contact. Os metais, especialmente o níquel, são os sensibilizantes de contato mais comuns em crianças. Dados recentes revelam aumento na incidência da alergia deste em países industrializados. A sensibilização pode ocorrer em qualquer idade, mesmo em recém-nascidos. Bijuterias, especialmente brincos nas orelhas, são ligadas ao aumento da sensibilização ao níquel. A sensibilização ao cobalto geralmente ocorre pelo uso de bijuterias. A fonte mais comum de sensibilização ao cromo é o couro. Devido à ausência de terapia específica, o principal tratamento consiste em identificar e evitar os alérgenos responsáveis. Este artigo pretende apresentar uma visão atualizada sobre os aspectos epidemiológicos e clínicos da alergia de contato aos metais, focando estratégias de prevenção e fatores de risco, além de alertar sobre as possíveis e novas fontes de contato.